Thrilling summer adventure: Bali Tourism Polytechnic explores Penang's hospitality hub! / Anderson Ngelambong … [et al.] - Ngelambong, Anderson; Ahmad, Johanna Adlin; Mohamed Rani, Zaharah; Rahim, Noraini (UiTM Global @ Office of International Affairs, 2024)
A summer programme was hosted by the Faculty of Hotel and Tourism Management, UiTM Pulau Pinang Branch, from the 14 to 20 May 2023. The programme offered diverse academic, cultural, and recreational pursuits for participants from Bali Tourism Politeknik (BiTP). Three BiTP lecturers, Dr. Putu Utama, Dr Luh Yusni Wiarti, and Dr Widi Hardini, attended this programme. The programme also received ten postgraduate students who accompanied them to the programme. The participants stayed on campus at Hotel UiTM Pulau Pinang Branch throughout the week-long programme.